Developing a toolkit for implementing evidence-based guidelines to manage hypertension and diabetes in Cambodia: a descriptive case study - Nirmali Sivapragasam; David B. Matchar; Pheak Chhoun; Hero Kol; Chhun Loun; Amina Mahmood Islam; John Ansah; Siyan Yi (BMC, 2022)
Abstract Background In Cambodia, economic development accompanied by health reforms has led to a rapidly ageing population and an increasing incidence and prevalence of noncommunicable diseases. National strategic plans recognize primary care health centres as the focal points of care for treating and managing chronic conditions, particularly hypertension and type 2 diabetes. However, health centres have limited experience in providing such services. This case study describes the process of developing a toolkit to facilitate the use of evidence-based guidelines to manage hypertension and type 2 diabetes at the health-centre level. Methods We developed and revised a preliminary toolkit based on the feedback received from key stakeholders. We gathered feedback through an iterative process of group and one-to-one consultations with representatives of the Ministry of Health, provincial health department, health centres and nongovernmental organizations between April 2019 and March 2021. Results A toolkit was developed and organized according to the core tasks required to treat and manage hypertension and type 2 diabetes patients. The main tools included patient identification and treatment cards, risk screening forms, a treatment flowchart, referral forms, and patient education material on risk factors and lifestyle recommendations on diet, exercise, and smoking cessation. The toolkit supplements existing guidelines by incorporating context-specific features, including drug availability and the types of medication and dosage guidelines recommended by the Ministry of Health. Referral forms can be extended to incorporate engagement with community health workers and patient education material adapted to the local context. All tools were translated into Khmer and can be modified as needed based on available resources and arrangements with other institutions. Conclusions Our study demonstrates how a toolkit can be developed through iterative engagement with relevant stakeholders individually and in groups to support the implementation of evidence-based guidelines. Such toolkits can help strengthen the function and capacity of the primary care system to provide care for noncommunicable diseases, serving as the first step towards developing a more comprehensive and sustainable health system in the context of population ageing and caring for patients with chronic diseases.